An exact dynamic stiffness method for multibody systems consisting of beams and rigid-bodies. (March 2021) - Liu, Xiang; Sun, Chengli; Ranjan Banerjee, J.; Dan, Han-Cheng; Chang, Le
Highlights: Dynamic stiffness model for multi-body systems consisting of beams and rigid bodies. General rigid bodies connected to beams at arbitrary positions with arbitrary angles. General beam theories (Euler-Bernoulli, Timoshenko and etc) satisfied exactly. Exact for all frequencies and benchmark modal solutions provided. High computational efficiency which is at least 100 times faster than ANSYS. Abstract: An exact dynamic stiffness method is proposed for the free vibration analysis of multi-body systems consisting of flexible beams and rigid bodies. The theory is sufficiently general in that the rigid bodies can be of any shape or size, but importantly, the theory permits connections of the rigid bodies to any number beams at any arbitrary points and oriented at any arbitrary angles. For beam members, a range of theories including the Bernoulli-Euler and Timoshenko theories are applied. The assembly procedure for the beam and rigid body properties is simplified without resorting to matrix inversion. The difficulty generally encountered in computing the problematic J 0 count when applying the Wittrick-Williams algorithm for modal analysis has been overcome. Applications of different beam theories for both axial and bending vibrations have enabled the examination of the role played by rigid-body parameters on the multi-body system's dynamic behaviour. Some exact benchmark results are provided and compared with published results and with finite element solutions. This research provides an exact and highly efficient analysis tool for multibody system dynamics which is for the free vibration analysis, ideally suited for optimization and inverse problems such as modal parameter identification.